The Effect of Sodium Propionate Addition, Type of Packaging and Duration of Storage on Iodine Content and the Quality of Seaweed (Euchemma cattonii) Jelly Candy - Rina Warastuti; Evy Damayanthi; Cesilia Meti Dwiriani (Media Gizi dan Keluarga, 2000)
The purpose of this research’s to study utilization of seaweed (Euchemma cattonii) for producing jelly candy, and to analyse the effect of sodium propionate addition, type of packaging and storage on iodine content of seaweed jelly candy. The preliminary step was conducted to formulate seaweed jelly candy which is mostly prefered through organoleptic test. The organoleptic test revealed that formula 1 was the mostly prefered. The gel dow composition are gelatin (8 g), water (13), HFS-55 (35 g), sucrose (10 g), essence (0.18 g), food colour (0.12 g), citrate acid (0.5 g) and antifoam (0.005 g), whereas the seaweed dow consist of seaweed and water (26 g), sucrose (7 g), essence (0.7 g). The result of analysist variance showed that sodium propionate addition effected on iodine content. Type of packaging used has shown influenced total sugar, while duration of storege effected iodine, water and total sugar of seaweed jelly candy. Sodium propionate, type of packaging and duration of storage has influenced total acid of seaweed jelly candyKeywords: stotage, iodine, seawed.